Sampling Errors and Portfolio Efficient Analysis - Kroll, Yoram; Levy, Haim (Journal of Financial and Quantitative Analysis, 1980)
Studies which deal with portfolio efficiency analysis can be divided into two main categories: (a) those concerned with the development of normative decision rules; and (b) those that discuss the application of the normative rules to empirical data. Most of the research on portfolio efficiency analysis uses some set of empirical data, without considering the possible errors which may arise when a sample rather than the entire population is examined. The prevailing neglect of the sampling errors is a clear reflection of the complexity of the issue.